2007
DOI: 10.4049/jimmunol.178.1.520
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Transmigration through Brain Microvessel Endothelium Is Regulated by MIP-1α Chemokine and Matrix Metalloproteinases

Abstract: Dendritic cells (DCs) accumulate in the CNS during inflammatory diseases, but the exact mechanism regulating their traffic into the CNS remains to be defined. We now report that MIP-1α increases the transmigration of bone marrow-derived, GFP-labeled DCs across brain microvessel endothelial cell monolayers. Furthermore, occludin, an important element of endothelial tight junctions, is reorganized when DCs migrate across brain capillary endothelial cell monolayers without causing significant changes in the barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
80
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 98 publications
8
80
0
Order By: Relevance
“…These Cop-1-breakdown products may themselves be neuroprotective, and may be capable of crossing the BBB to mediate their neuroprotective effects. Moreover, these DC can amplify a T cellmediated immune response in the CNS [59], which can further potentiate neuroprotective effects of Cop-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These Cop-1-breakdown products may themselves be neuroprotective, and may be capable of crossing the BBB to mediate their neuroprotective effects. Moreover, these DC can amplify a T cellmediated immune response in the CNS [59], which can further potentiate neuroprotective effects of Cop-1.…”
Section: Discussionmentioning
confidence: 99%
“…These Cop-1-breakdown products may themselves be neuroprotective, and may be capable of crossing the BBB to mediate their neuroprotective effects. Moreover, these DC can amplify a T cellmediated immune response in the CNS [59], which can further potentiate neuroprotective effects of Cop-1.These data, taken together, provide a novel mechanism of Cop-1 mediated neuroprotection, enhancing its utility for treatment of neurodegenerative and neuroinflammatory disorders. …”
mentioning
confidence: 90%
“…(Christian et al, 1996), we have found no evidence for the presence of plasmacytoid dendritic cells during the first 14 days after VSV infection (Palian et al, unpublished). Indeed, pDCs are reportedly absent from the brain parenchyma, but have been found in brain during chronic inflammation (Ambrosini et al, 2005;Bailey et al, 2007;Matyszak and Perry, 1997;Newman et al, 2005;Rosicarelli et al, 2005;Serafini et al, 2006;Zozulya et al, 2007). IFN-producing cells do not enter the CNS at early times after infection by wt VSV, and peripheral IFN does not cross the blood-brain barrier efficiently (Dafny and Yang, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…6A) supports this notion. Also, it is tempting to speculate that at proinflammatory doses S100B, by inducing CCL3 expression in microglia, not only might participate in stimulation of microglia migration to the site of damage; it might increase the transmigration of blood-borne inflammatory cells across brain capillaries (77).…”
Section: Discussionmentioning
confidence: 99%